Efficiency and persistence of fungicides in the control of powdery mildew of wheat through seed treatment Eficiência e persistência de fungicidas no controle do oídio do trigo via tratamento de sementes - Reis E.M. (2008)
Wheat powdery mildew has been frequently detected in high intensities in wheat fields seeded with susceptible cultivars in southern Brazil. In experiment conducted in greenhouse the persistence of the fungicides difenoconazol, flutriafol, triadimenol, and triticonazol were assessed at three rates of commercial formulation, applied as seed treatment to control powdery mildew. Wheat seeds of cultivar BR 23, susceptible to powdery mildew, were treated with fungicides and seeded in plastic pots having soil-sand-vermiculite as substrate. Wheat plants previously inoculated with the fungus were kept among the plants to be inoculated as primary inoculum source. Evaluations were per formed daily in the main tiller from the appearance of the first powdery mildew colonies. Disease was quantified through incidence up to the growth stage of four fully expanded leaves. Disease progress curves for each fungicide and their three rates were adjusted to the logistic model in increasing order of effectiveness, higher fungicidal protection was reached by seeds treatment with, difenoconazol, flutriafol, trticonazol, and triadimenol.